Systematic review and meta-analysis of birth weight and prenatal exposure to perfluoroundecanoic acid - Hongyu Ru; Paige A. Bommarito; Michael W. Dzierlenga; Alexandra L. Lee; Kristen M. Rappazzo; Benjamin J.K. Davis; Avanti V. Shirke; Alexis Agbai; Elizabeth G. Radke; Thomas F. Bateson; J. Michael Wright (Environmental Research, 2026)

Optimizing coral reef monitoring: species traits and habitat factors predict visual census performance - Iris M. George; Alexandra C. D. Davis; John L. Akins; Allison C. Candelmo; Stephanie J. Green (Coral Reefs, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Corrigendum to “Association between summertime emergency department visits and maximum daily heat index in rural and non-rural areas of Virginia (2015–2022)” [Sci. Total Environ. Volume 948 (2024) 174753] - Antonia Mendrinos; Janice O'Brien; Meredith Davis; Alexandra Baldwin; Benjamin F. Zaitchik; Annie Britton; Immaculata Mwanja; Julia M. Gohlke (Science of The Total Environment, 2026)

Characterization of N-arylamide insecticides to control populations of the green peach aphid, Myzus persicae - Flinn M. O'Hara; Sarah E. Mccomic; Zhijun Liu; Alexandra Cremades; Jeffrey A. Davis; Edmund J. Norris; Jeffrey R. Bloomquist; Daniel R. Swale (Pesticide Biochemistry and Physiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Association between summertime emergency department visits and maximum daily heat index in rural and non-rural areas of Virginia (2015–2022) - Antonia Mendrinos; Janice O'Brien; Meredith Davis; Alexandra Baldwin; Benjamin F. Zaitchik; Annie Britton; Immaculata Mwanja; Julia M. Gohlke (Science of The Total Environment, 2024)

Metal and metalloid maternal transfer in a newborn West Indian manatee (Trichechus manatus) two years after the northeastern oil spill disaster of 2019 in Brazil - Leila S. Lemos; Fernanda L.N. Attademo; Lauro Henrique de Paiva; Alexandra F. Costa; Laura M.A. Reis; Fábia de Oliveira Luna; Rachel Ann Hauser-Davis; Salvatore Siciliano (Marine Pollution Bulletin, 2024)

Experiences of and support for black women in ecology, evolution, and marine science - Nikki Traylor-Knowles; Anamica Bedi de Silva; Anjali D. Boyd; Karlisa A. Callwood; Alexandra C. D. Davis; Giselle Hall; Victoria Moreno; Cinda P. Scott (Frontiers in Marine Science, 2023)
Systemic racism and sexism are well documented in ecology, evolution, and marine science. To combat this, institutions are making concerted efforts to recruit more diverse people by focusing on the recruitment of Black people. However, despite these initiatives, white supremacy culture still prevails. The retention of Black people in ecology, evolution, and marine science has not increased in the ways that were hoped for. This is particularly true for Black women, who struggle to find a safe working environment that values their contributions and allows them to openly celebrate their own culture and identity. In this perspective article, we discuss the challenges that Black women face every day, and the needs of Black women to thrive in ecology, evolution, and marine science. We have written this directly to Black women and provide information on not only our challenges, but our stories. However, readers of all identities are welcome to listen and examine their role in perpetuating systemic racism and sexism. Lastly, we discuss support mechanisms for navigating ecology, evolution, and marine science spaces so that Black women can thrive.

Effects of a School-Based Garden Program on Academic Performance: A Cluster Randomized Controlled Trial - Jaimie N. Davis; Katie Nikah; Matthew J. Landry; Sarvenaz Vandyousefi; Reem Ghaddar; Matthew Jeans; Michele Hockett Cooper; Bonnie Martin; Lyndsey Waugh; Shreela V. Sharma; Alexandra E. van den Berg (Journal of the Academy of Nutrition and Dietetics, 2023)

Re-Envisioning Undergraduate Research Experiences to Increase Diversity, Equity, and Inclusion, and Harness the Power of Diversity in Ocean Sciences - Paul Barber; Catalina Martinez; Corey Garza; Deidre Gibson; Alexandra Davis (Oceanography, 2023)
Diversity in ocean sciences lags far behind US demographics. A substantial body of research highlights barriers that limit the participation and success of students from underrepresented minoritized (URM) and other marginalized groups in STEM disciplines, and a wealth of studies highlight successful interventions that improve the persistence of these groups in STEM higher education. Despite this knowledge, over the past four decades, ocean sciences has made limited progress in growing diversity within its workforce, suggesting new strategies are needed. Undergraduate research experiences are a pivotal pathway toward graduate education and future careers in ocean sciences, but they are plagued by many issues that limit the participation and success of persons from URM and other marginalized backgrounds. Here we summarize obstacles that limit participation of diverse populations in ocean sciences and highlight successful strategies for overcoming these obstacles. By re-envisioning how we approach undergraduate research experiences and bringing intentionality to the recruitment of students and the training environments that they experience, we can more effectively grow diversity in ocean sciences and unleash the power of diversity to address the pressing local and global problems facing marine ecosystems.

Advancing Diversity and Inclusivity in Ocean Sciences by Re-Envisioning Overlooked Barriers in Scientific Diving Training - Paul Barber; Jeannie Barber-Choi; Austin Betancourt; Benjamin Cuker; Alexandra Davis; Caitlin Fong; Peggy Fong; Deidre Gibson; Tyler Smith (Oceanography, 2023)
Self-contained underwater breathing apparatus (scuba) is an essential tool in some marine science fields. However, financial costs and racial disparities in swimming participation can be a barrier to entry for many aspiring marine scientists of color. Scientific diving programs could improve access to scientific diving training by offering training as part of their standard undergraduate curriculum and by maintaining a stock of scuba gear for use during courses. Similarly, the American Academy of Underwater Scientists (AAUS) could make training more accessible by re-envisioning components of the swim test and by building water safety skills into AAUS training—​all without compromising safety. Combined, these two actions would expand pathways for students of color to careers in marine science, adding much needed diversity to the field.

Correction to: Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2022)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Genome variations between rhizosphere and bulk soil ecotypes of a Pseudomonas koreensis population - Lucas Dantas Lopes; Michele de C. Pereira e Silva; Alexandra J. Weisberg; Edward W. Davis; Qing Yan; Camila de S. Varize; Chih‐Feng Wu; Jeff H. Chang; Joyce E. Loper; Fernando D. Andreote (Environmental Microbiology, 2018)
Summary Bulk soil and rhizosphere are soil compartments selecting different microbial communities. However, it is unknown whether this selection also can change the genome content of specific bacterial taxa, splitting a population in distinct ecotypes. To answer this question we compared the genome sequences of 53 isolates obtained from sugarcane rhizosphere (28) and bulk soil (25). These isolates were previously classified in the Pseudomonas koreensis subgroup of the P. fluorescens complex. Phylogenomics showed a trend of separation between bulk soil and rhizosphere isolates. Discriminant analysis of principal components (DAPC) identified differences in the accessory genome of rhizosphere and bulk soil sub‐populations. We found significant changes in gene frequencies distinguishing rhizosphere from bulk soil ecotypes, for example, enrichment of phosphatases and xylose utilization ( xut ) genes, respectively. Phenotypic assays and deletion of xutA gene indicated that accumulation of xut genes in the bulk soil sub‐population provided a higher growth capacity in a d ‐xylose medium, supporting the corresponding genomic differences. Despite the clear differences distinguishing the two ecotypes, all 53 isolates were classified in a single 16S rRNA gene OTU. Collectively, our results revealed that the gene pool and ecological behavior of a bacterial population can be different for ecotypes living in neighbouring soil habitats.

Differential effects of native vs. invasive predators on a common Caribbean reef fish - Alexandra C. D. Davis (Environmental Biology of Fishes, 2018)

Tropical soils are a reservoir for fluorescent Pseudomonas spp. biodiversity - Lucas Dantas Lopes; Edward W. Davis; Michele de C. Pereira e Silva; Alexandra J. Weisberg; Luana Bresciani; Jeff H. Chang; Joyce E. Loper; Fernando D. Andreote (Environmental Microbiology, 2018)
Summary Fluorescent Pseudomonas spp. are widely studied for their beneficial activities to plants. To explore the genetic diversity of Pseudomonas spp. in tropical regions, we collected 76 isolates from a Brazilian soil. Genomes were sequenced and compared to known strains, mostly collected from temperate regions. Phylogenetic analyses classified the isolates in the P. fluorescens (57) and P. putida (19) groups. Among the isolates in the P. fluorescens group, most (37) were classified in the P. koreensis subgroup and two in the P. jessenii subgroup. The remaining 18 isolates fell into two phylogenetic subclades distinct from currently recognized P. fluorescens subgroups, and probably represent new subgroups. Consistent with their phylogenetic distance from described subgroups, the genome sequences of strains in these subclades are asyntenous to the genome sequences of members of their neighbour subgroups. The tropical isolates have several functional genes also present in known fluorescent Pseudomonas spp. strains. However, members of the new subclades share exclusive genes not detected in other subgroups, pointing to the potential for novel functions. Additionally, we identified 12 potential new species among the 76 isolates from the tropical soil. The unexplored diversity found in the tropical soil is possibly related to biogeographical patterns.

Type I interferon as a biomarker in autoimmunity and viral infection: a leukocyte subset-specific analysis unveils hidden diagnostic options - Romy Strauß; Thomas Rose; Shaun M. Flint; Jens Klotsche; Thomas Häupl; Markus Peck-Radosavljevic; Taketoshi Yoshida; Chieko Kyogoku; Alexandra Flechsig; Amy M. Becker; Kathryn H. Dao; Andreas Radbruch; et al. (Journal of Molecular Medicine, 2017)

Patient and genetic counselor perceptions of in-person versus telephone genetic counseling for hereditary breast/ovarian cancer - Aryana S. Jacobs; Marc D. Schwartz; Heiddis Valdimarsdottir; Rachel H. Nusbaum; Gillian W. Hooker; Tiffani A. DeMarco; Jessica E. Heinzmann; Wendy McKinnon; Shelley R. McCormick; Claire Davis; Andrea D. Forman; Alexandra Perez Lebensohn; et al. (Familial Cancer, 2016)

Use of a Rapid Ethylene Glycol Assay: a 4-Year Retrospective Study at an Academic Medical Center - Sydney L. Rooney; Alexandra Ehlers; Cory Morris; Denny Drees; Scott R. Davis; Jeff Kulhavy; Matthew D. Krasowski (Journal of Medical Toxicology, 2016)

Characterisation of the clinical and activated T cell response to repeat delayed-type hypersensitivity skin challenges in human subjects, with KLH and PPD, as a potential model to test T cell-targeted therapies - Alexandra Belson; Tim Schmidt; Disala Fernando; Kelly Hardes; Nicola Scott; Sara Brett; Deborah Clark; João Joaquim Oliveira; Bill Davis; Simon McHugh; John Stone (Inflammation Research, 2016)

California forests show early indications of both range shifts and local persistence under climate change - Josep M. Serra‐Diaz; Janet Franklin; Whalen W. Dillon; Alexandra D. Syphard; Frank W. Davis; Ross K. Meentemeyer (Global Ecology and Biogeography, 2016)
Aim Forest regeneration data provide an early signal of the persistence and migration of tree species, so we investigated whether species shifts due to climate change exhibit a common signal of response or whether changes vary by species. Location California Floristic Province, United States ; mediterranean biome. Methods We related Forest Inventory and Analysis ( FIA ) data from 2000−07 for 13 tree species to high‐resolution climate and geographical data. Using methods from invasion ecology, we derived indices of species‐specific regeneration overlap and central tendency change (range‐wide global indicators) based on kernel density estimation of presence and absence of regeneration. We then built regeneration surfaces to identify areas of occurrence of high regeneration (regeneration hotspots, local indicators) in both geographical and climate space for 13 common tree species. Results Differences between presence and absence of regeneration in forests varied in magnitude across species, with little evidence that tree regeneration is shifting to higher latitudes and elevations, the expected geographical fingerprint of climate change. We also identified potential topographic mediators of regeneration dynamics. Multiple regeneration hotspots were found for many species, suggesting the influence of non‐climatic factors on regeneration. Differences between the presence and absence of regeneration in geographic and climate spaces were not always congruent, suggesting that shifting climate space and range area are not entirely coupled. Main conclusions The distributions of regeneration in Californian forests show diverse signals, not always tracking the higher latitudinal–elevation fingerprint of climate change. Local regeneration hotspots are common in our analysis, suggesting spatially varying persistence of forest linked to natural and anthropogenic disturbances. Our results emphasize that projections of tree range shifts in the context of climate change should consider the variation of regeneration drivers within species ranges, beyond the overall climate signal.

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Evolutionary refugia and ecological refuges: key concepts for conserving Australian arid zone freshwater biodiversity under climate change - Jenny Davis; Alexandra Pavlova; Ross Thompson; Paul Sunnucks (Global Change Biology, 2013)
Refugia have been suggested as priority sites for conservation under climate change because of their ability to facilitate survival of biota under adverse conditions. Here, we review the likely role of refugial habitats in conserving freshwater biota in arid Australian aquatic systems where the major long‐term climatic influence has been aridification. We introduce a conceptual model that characterizes evolutionary refugia and ecological refuges based on our review of the attributes of aquatic habitats and freshwater taxa (fishes and aquatic invertebrates) in arid Australia. We also identify methods of recognizing likely future refugia and approaches to assessing the vulnerability of arid‐adapted freshwater biota to a warming and drying climate. Evolutionary refugia in arid areas are characterized as permanent, groundwater‐dependent habitats (subterranean aquifers and springs) supporting vicariant relicts and short‐range endemics. Ecological refuges can vary across space and time, depending on the dispersal abilities of aquatic taxa and the geographical proximity and hydrological connectivity of aquatic habitats. The most important are the perennial waterbodies (both groundwater and surface water fed) that support obligate aquatic organisms. These species will persist where suitable habitats are available and dispersal pathways are maintained. For very mobile species (invertebrates with an aerial dispersal phase) evolutionary refugia may also act as ecological refuges. Evolutionary refugia are likely future refugia because their water source (groundwater) is decoupled from local precipitation. However, their biota is extremely vulnerable to changes in local conditions because population extinction risks cannot be abated by the dispersal of individuals from other sites. Conservation planning must incorporate a high level of protection for aquifers that support refugial sites. Ecological refuges are vulnerable to changes in regional climate because they have little thermal or hydrological buffering. Accordingly, conservation planning must focus on maintaining meta‐population processes, especially through dynamic connectivity between aquatic habitats at a landscape scale.

Modeling plant species distributions under future climates: how fine scale do climate projections need to be? - Janet Franklin; Frank W. Davis; Makihiko Ikegami; Alexandra D. Syphard; Lorraine E. Flint; Alan L. Flint; Lee Hannah (Global Change Biology, 2013)
Recent studies suggest that species distribution models ( SDM s) based on fine‐scale climate data may provide markedly different estimates of climate‐change impacts than coarse‐scale models. However, these studies disagree in their conclusions of how scale influences projected species distributions. In rugged terrain, coarse‐scale climate grids may not capture topographically controlled climate variation at the scale that constitutes microhabitat or refugia for some species. Although finer scale data are therefore considered to better reflect climatic conditions experienced by species, there have been few formal analyses of how modeled distributions differ with scale. We modeled distributions for 52 plant species endemic to the C alifornia F loristic P rovince of different life forms and range sizes under recent and future climate across a 2000‐fold range of spatial scales (0.008–16 km 2 ). We produced unique current and future climate datasets by separately downscaling 4 km climate models to three finer resolutions based on 800, 270, and 90 m digital elevation models and deriving bioclimatic predictors from them. As climate‐data resolution became coarser, SDM s predicted larger habitat area with diminishing spatial congruence between fine‐ and coarse‐scale predictions. These trends were most pronounced at the coarsest resolutions and depended on climate scenario and species' range size. On average, SDM s projected onto 4 km climate data predicted 42% more stable habitat (the amount of spatial overlap between predicted current and future climatically suitable habitat) compared with 800 m data. We found only modest agreement between areas predicted to be stable by 90 m models generalized to 4 km grids compared with areas classified as stable based on 4 km models, suggesting that some climate refugia captured at finer scales may be missed using coarser scale data. These differences in projected locations of habitat change may have more serious implications than net habitat area when predictive maps form the basis of conservation decision making.